The Role of Prophetic Guidance in Promoting Sustainable Peace Values - Al-Khuza’i, Fari’a Abdullah Ghotish; Ibrahim, Hanadi Eisa Mohana (Journal of Educational and Psychological Sciences, 2025)
This study investigated the role of Prophetic guidance in promoting sustainable peace by analyzing relevant Sunnah texts using a qualitative analytical approach. The findings show that the Prophet Muhammad’s (ﷺ) methods such as dialogue, compassion, avoiding harm, and social solidarity serve as effective tools for fostering psychological and social stability. The Sunnah offers a comprehensive vision of peace grounded in justice, dignity, and community cohesion. The study recommends integrating Prophetic principles into educational and counseling programs and encourages further field research on their impact in post-conflict settings.